Susceptibility of male reproductive system to bisphenol A, an endocrine disruptor: Updates from epidemiological and experimental evidence. Issue 4 (16th December 2022) - Yadav, Shiv K.; Bijalwan, Vandana; Yadav, Suresh; Sarkar, Kamalesh; Das, Santasabuj; Singh, Dhirendra P.
Abstract: Bisphenol A (BPA) is an omnipresent environmental pollutant. Despite being restrictions in‐force for its utilization, it is widely being used in the production of polycarbonate plastics and epoxy resins. Direct, low‐dose, and long‐term exposure to BPA is expected when they are used in the packaging of food products and are used as containers for food consumption. Occupationally, workers are typically exposed to BPA at higher levels and for longer periods during the manufacturing process. BPA is a known endocrine disruptor chemical (EDC), that causes male infertility, which has a negative impact on human life from emotional, physical, and societal standpoints. To minimize the use of BPA in numerous consumer products, efforts and regulations are being made. Despite legislative limits in numerous nations, BPA is still found in consumer products. This paper examines BPA's overall male reproductive toxicity, including its impact on the hypothalamic‐pituitary‐testicular (HPT) axis, hormonal homeostasis, testicular steroidogenesis, sperm parameters, reproductive organs, and antioxidant defense system. Furthermore, this paper highlighted the role of non‐monotonic dose–response (NMDR) in BPA exposure, which will help to improve the overall understanding of the harmful effects of BPA on the male reproductive system.